Influence of Fluorine Substitution on the Optical, Thermal, Electrochemical and Structural Properties of Carbazole-Benzothiadiazole Dicarboxylic Imide Alternate Copolymers - R. Murad, Ary (Polymers (Basel), 2020)
In this work four novel donor-acceptor copolymers, PCDTBTDI-DMO, PCDTBTDI-8, P2F-CDTBTDI-DMO and P2F-CDTBTDI-8, were designed and synthesised via Suzuki polymerisation. The first two copolymers consist of 2,7-carbazole flanked by thienyl moieties as the electron donor unit and benzothiadiazole dicarboxylic imide (BTDI) as electron acceptor units. In the structures of P2F-CDTBTDI-DMO and P2F-CDTBTDI-8 copolymers, two fluorine atoms were incorporated at 3,6-positions of 2,7-carbazole to investigate the impact of fluorine upon the optoelectronic, structural and thermal properties of the resulting polymers. P2F-CDTBTDI-8 possesses the highest number average molecular weight (M(n) = 24,200 g mol(−1)) among all the polymers synthesised. PCDTBTDI-DMO and PCDTBTDI-8 show identical optical band gaps of 1.76 eV. However, the optical band gaps of fluorinated copolymers are slightly higher than non-fluorinated counterparts. All polymers have deep-lying highest occupied molecular orbital (HOMO) levels. Changing the alkyl chain substituents on BTDI moieties from linear n-octyl to branched 3,7-dimethyloctyl groups as well as substituting the two hydrogen atoms at 3,6-positions of carbazole unit by fluorine atoms has negligible impact on the HOMO levels of the polymers. Similarly, the lowest unoccupied molecular orbital (LUMO) energy levels are almost comparable for all polymers. Thermogravimetric analysis (TGA) has shown that all polymers have good thermal stability and also confirmed that the fluorinated copolymers have higher thermal stability relative to those non-fluorinated analogues. Powder X-ray diffraction (XRD) studies proved that all polymers have an amorphous nature in the solid state.